2002
DOI: 10.1071/ea02018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of artificial wind shelters on the growth and yield of rainfed crops

Abstract: There is great interest in quantifying and understanding how shelter modifies crop growth and development under Australian conditions. Small constructed enclosures (shelters) can consistently reduce wind speed, allowing experiments to be run with replicated sheltered and unsheltered treatments in close proximity. The aim of this study was to quantify the effect on microclimate of consistently reducing wind speed by 70% and explain the consequences for dryland wheat (Triticum aestivum), lupin (Lupinus angustifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…APSIM EO v. SCAM Sudmeyer et al (2002) showed that wind speed within the artificial enclosures was reduced by about 70% regardless of season or location. This represents the maximum wind reduction possible by windbreaks and data from these experiments is ideally suited to benchmark model responses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…APSIM EO v. SCAM Sudmeyer et al (2002) showed that wind speed within the artificial enclosures was reduced by about 70% regardless of season or location. This represents the maximum wind reduction possible by windbreaks and data from these experiments is ideally suited to benchmark model responses.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical approaches described above were tested against field data from artificial shelter experiments (Sudmeyer et al 2002). The data consisted of detailed environmental measurements of crop growth and yield for wheat and mungbean taken from artificial enclosures in south-eastern Queensland and in south-eastern Western Australia.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to protecting against strong winds, these forests also create micrometeorological environments, typically including a heat reserving effect of 1-4 C. The construction of wind protection forests is also highly desirable to protect farmlands that similarly experience wind damage to crops, arable land and other facilities; these include riverside, plateau and mountain foot areas (An 2006). There are many studies on the effects of windbreaks on the growth of potato plants (Sun and Dickinson 1997), the yields of wheat, lupin and mungbean (Sudmeyer et al 2002) and the yield of wheat plants (Campi et al 2009).…”
Section: Introductionmentioning
confidence: 99%